Cactus Nurseries and Conservation in a Biosphere Reserve in Mexico - Pulido, María T.; Cuevas-Cardona, Consuelo (Ethnobiology Letters, 2013)
Documenting how socio-ecosystem conservation knowledge and practice arise and are modified are issues of ethnobiological interest. In the Barranca de Metztitlán Biosphere Reserve (RBBM), plant nurseries, some of which were created as Environmental Management Units (UMAs), have been established to grow and conserve cacti. This paper describes these nurseries, their role in cactus conservation, and the benefits and limitations for the people managing them. The nurseries have helped decrease illegal traffic in cacti and have enabled ex situ conservation of 22 cacti species. Cactus management has changed from extraction to cultivation, as a result of the knowledge and actions of multiple actors. The main limitation is marketing, a recurring problem for non-timber forest products (NTFP). Greater coordination among stakeholders is recommended, such as involvement by non-governmental organizations to improve their probability of success, as well as learning from the experience of other cactus UMAs. Improving the market for cacti is an issue that needs an immediate solution; otherwise conservation efforts could relapse.